Long-range transport and microscopy analysis of Sangay volcanic ashes in Ecuador - Daniel Moran-Zuloaga; Wilson Merchan-Merchan; Emilio Rodriguez-Caballero; Maurizio Mulas; Philip Hernick (Air Quality, Atmosphere & Health, 2024)
This study aims to conduct a spatiotemporal analysis of the long-range transportation of volcanic ashes that originates from the eruption of the Sangay volcano and reached Guayaquil during the months of June 2020; September 2020; and April 2021. The particulate matter data (PM 2.5 ) was obtained using a low-cost air quality sensor. During the wet season of 2020 (Jan–May), PM 2.5 average concentrations were 6 ± 2 μg m −3 while during the dry season of 2020 (July–Nov), PM 2.5 average concentrations were 16 ± 3 μg m −3 in Guayaquil. The most prominent plumes occurred on September 20th of 2020, a month with no rain but high wind speeds created by the Andes Mountain topography to the coast. During this event, PM 2.5 concentrations started at 12:00 UTC-5 in a volcanic plume event that lasted 4 h with a maximum peak of 133 + 40 μg m −3 . Electron microscopy of selected samples showed that the ashes of the three eruptions may differ in size and morphology. EDX analysis reveals that the ash contains certain elements—C, Si, Na, Mg, Al, Ca, S, and Fe—in similar proportions. In summary, this study remarks on the meteorological role and the long-range transport of Sangay volcanic ashes.

Overview and Seasonality of PM10 and PM2.5 in Guayaquil, Ecuador - Daniel Moran-Zuloaga; Wilson Merchan-Merchan; Emilio Rodríguez-Caballero; Philip Hernick; Julio Cáceres; Mauricio H. Cornejo (Aerosol Science and Engineering, 2021)
The focus of this study is the assessment of total suspended particles (TSP) and particulate matter (PM) with various aerodynamic diameters in ambient air in Guayaquil, a city in Ecuador that features a tropical climate. The urban annual mean concentrations of TSP (Total Suspended Particles), and particle matter (PM) with various aerodynamic diameters such as: PM 10 , PM 2.5 and PM 1 are 31 ± 14 µg m −3 , 21 ± 9 µg m −3 , 7 ± 2 µg m −3 and 1 ± 1 µg m −3 , respectively. Air mass studies reveal that the city receives a clean Southern Ocean breeze. Backward trajectory analysis show differences between wet and dry seasons. During the dry season, most winds come from the south and southwest, while air masses from the peri urban may contribute as pollutant sources during the wet season. Although mean values of PM 10 and PM 2.5 were below dangerous levels, our year-round continuous monitoring study reveals that maximum values often surpassed those permissible limits allowed by the Ecuadorian norms. A cluster analysis shows four main paths in which west and southwest clusters account for more than 93% of the pollution. Total vertical column of NO 2 shows the pollution footprint is strongest during the dry season, as opposed to the wet season. A microscopic morphological characterization of ambient particles within the city during the wet and the dry season reveals coarse mode particles with irregular and rounded shapes. Particle analysis reveals that samples are composed of urban dust, anthropogenic and organic debris during the dry season while mainly urban dust during the wet season.